More is better? Constructed wetlands filled with different amount of Fe oxides showed opposite phosphorus removal performance. (20th December 2021) - Hu, Xiaojin; Wan, Xiaodong; Tan, Wei; Xie, Huijun; Zhuang, Linlan; Zhang, Jian; Liang, Shuang; Hu, Zhen
Abstract: Iron (Fe) oxides (limonite) could nourish iron reducing bacteria (IRB) and increase the available electron in constructed wetland (CW) system with the cycling between Fe(Ⅱ) and Fe(Ⅲ). However, whether the enrichment of IRB could induce "side-effect" of P release is unclear. In the present study, vertical subsurface CW microcosm without limonite (CWA), with low amount (5%) of limonite (CWB), and high amount (15%) of limonite (CWC) were built in order to investigate the effect of addition amount of limonite on the removal performance of P. The addition of limonite significantly improved removal efficiencies of NH4 –N, NO3 –N, TN (p ≤ 0.05) in CWB and CWC, and except for NH4 –N, the removal performance of NO3 –N and TN was enhanced in CWC due to the increased amount of limonite. While the removal efficiency of TP was the worst with the promoted limonite amount of CWC. Besides, the release of P occurred in the upper layer (35–55 cm from bottom) of CWC. The distribution of Fe 2+ and XPS results indicated the construction of Fe cycle in CWC. Although the quantities of bacteria 16S rRNA, and N related genes showed no difference between treated CWs and control group (p > 0.05), Illumina high-throughput sequencing analysis indicated the relative abundance of nitrifying and denitrifying bacteria as well as Fe related bacteria were higher in limonite-treated CWs. In addition, the quantity of phosphorus accumulating organisms (PAOs) in CWC was significantly lower than that of CWA and CWB, which is consistent with the result of water quality and microbial community of PAOs in upper layer of CWC. The results revealed that through active cycling of Fe between Fe(Ⅱ) and Fe(Ⅲ), the addition of limonite could enhance N removal while excessive limonite addition might induce the release of P. Graphical abstract: Image 1 Highlights: CWs filled with different amount of limonite both enhanced N removal. Excessive addition of limonite weakened P removal and induced the release of P. Enhanced N removal owed to the increased relative abundance of NOB, NRB, and IRB. Remobilization of excess Fe-bound P by IRB caused the release of P in upper layer.